The major innovations of Chinese economic development theories in the new era. Issue 1 (30th October 2018) - Hong, Yinxing
Abstract : Purpose: At present, the Chinese economy has entered the "new normal" phase with the transformation of development stages from the low-income to the middle-income ones. Accordingly, there appear a series of innovations in development theories. Innovations involve creative destructions. Therefore, innovative development theories at the present stage either deny the prevailing principles of development economics, or deny the theories that once effectively guided development at the low-income stage, or even sublate some of the development polices which were propelled and proved effective at the beginning of the reform and opening-up. The fundamental reason is that, as the development stages evolve, there occur new development tasks, new periodical characteristics and new laws of development. The paper aims to discuss these issues. Design/methodology/approach: Any development theory from abroad will find it difficult to correctly guide and clarify development problems in a socialist country, such as the huge population and the extreme imbalance between the urban and the rural and among regional developments. Findings: In conclusion, China, as a large world economy, has made innovations in its economic development theory, which indicates that it intends to perfect itself rather than seek hegemony. As the world's second largest economy, China should adapt to the transformation and further free people's minds instead of adhering to the old patterns of thinking. It should think over the path of development for a great world economy from the historical starting point of a large world economy and find development strategies to transform itself from a large economy to a great economy, so as to realize the dream of the Chinese nation to build a powerful country. Originality/value: Only political economy studies both the relations of production and the productive forces, and only a theory combining both can correctly guide China's economic development, which especially needs to be promoted by taking advantage of socialist economic system. Therefore, the first and foremost principle for a socialist political economy with Chinese characteristics is to insist on liberating and developing productive forces.